1989
DOI: 10.1063/1.344284
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous Biot waves in layered media

Abstract: A description, using transfer matrices, is given of the propagation of the three inhomogeneous Biot waves in layered porous media. This is applied to predict the surface impedance of porous layered materials at oblique incidence, and an example is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 11 publications
1
32
0
Order By: Relevance
“…For the verification of transfer matrix determined in this paper, justification of numerical computation and to study the effects of transversely isotropy, the calculations have been done for the case when both the porous layers are isotropic, i.e., by setting the values of e; d and g to be zero. The results in this situation should be in agreement with those obtained by Allard et al [7] and these are found so. The transverse isotropy of layers is found to increase both real and imaginary parts of the surface impedance.…”
Section: A Two-layered Anisotropic Porous Layered Mediumsupporting
confidence: 93%
See 2 more Smart Citations
“…For the verification of transfer matrix determined in this paper, justification of numerical computation and to study the effects of transversely isotropy, the calculations have been done for the case when both the porous layers are isotropic, i.e., by setting the values of e; d and g to be zero. The results in this situation should be in agreement with those obtained by Allard et al [7] and these are found so. The transverse isotropy of layers is found to increase both real and imaginary parts of the surface impedance.…”
Section: A Two-layered Anisotropic Porous Layered Mediumsupporting
confidence: 93%
“…Here, two layers of plastic foam are modelled as transversely isotropic porous layered medium. We adopted the values of physical parameters for the two layers of foam as given by Allard et al [7] and determined the values of the material coefficients used in this paper, by using the relations mentioned therein. The values of physical parameters for transversely isotropic porous medium can be obtained from those for isotropic one by the relations Using these values of material coefficients, the surface impedance is computed in the high-frequency range.…”
Section: A Two-layered Anisotropic Porous Layered Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there should be enough pores in the material for the sound to pass through and to get dampened. The porosity of a porous material is defined as the ratio of the volume of the voids in the material to its total volume (Allard et al 1989). Variable densities may result in different behavior of noise reduction since the density has great influence on the porosity of fibrous assemblies.…”
Section: Low-density Insulation Panelsmentioning
confidence: 99%
“…(Chin et al 1985) 1989 A simpler model was derived with transfer matrices which described the sinusoidal wave propagation in a layered porous material. (Allard et al 1989) 1993 A five parameters model, which yields the noise absorption coefficients of fiber webs as a function of their thickness and porosity. (Allard, Herzog et al 1993) 1993 Studied the wave propagation in an anisotropic layered fluid saturated porous medium backed by an impervious surface at oblique incidence (Sun et al 1993).…”
Section: Capillary Pore Modelmentioning
confidence: 99%